The impact of the COVID-19 pandemic on marriage and childbirth: Survey-based evidence from Iran - Mohammad Reza Farzanegan; Sven Fischer (Philipps-University Marburg, School of Business and Economics, 2023)
With a representative survey of 1,214 participants conducted in early 2022, this study investigates the impact of the COVID-19 pandemic on marriage and childbirth in Iran. The results of the empirical investigation using logistic regressions suggest that the experience of unemployment due to the pandemic is positively associated with marriage during the pandemic and the experience of losing a close relative or family member is negatively associated with marriage. In addition, concern about the persistence of the pandemic and vaccination status show negative associations with childbirth during the pandemic. We found heterogenous effects depending on gender, location, and social class; for example, the negative effects of the concern about a prolonged pandemic and vaccination status are driven by female respondents. Overall, the results have implications for the development of the fertility rate and population in post- pandemic Iran.
Keywords: C83; D91; D1; J12; J13; P46; Q54; 330; COVID-19; pandemic; disaster; Iran; survey; logistic regression; marriage; fertility; family planning; inequality